The identity of the crackling, luminescent frog of Suriname (Rana typhonia Linnaeus, 1758) (Amphibia, Anura) - Lavilla, Esteban Orlando (2010)
Review of the literature and recently available field notes from the collector of the type allows a reconsideration of the identity of the Linnaean name Rana typhonia. We provide evidence to demonstrate that the Linnaean species is neither a bufonid nor an Asiatic ranid, but a Neotropical hylid. Subsequently, we consider Rana typhonia as an older synonym of Rana venulosa Laurenti, 1768, redescribing its holotype under the new combination, Trachycephalus typhonius (Linnaeus, 1758).